Linear matrix inequalities control driven for non-ideal power source energy harvesting - Ferreira, Douglas C.; Chavarette, Fábio R. [UNESP]; Peruzzi, Nelson J. [UNESP] (Polish Society of Theoretical and Applied Mechanics, 2015)
The dynamic model of a linear energy harvester excited by a non-ideal power source is coupled to a controller to maximum vibration adjustment. Numerical analysis is taken to evaluate the energy harvested keeping the vibration optimized for the maximum interaction to the energy source using linear matrix inequalities for control driven. The dimensionless power output, actuation power and net output power is determined. As a result, it is possible to verify that the total energy harvested via exogenous vibration using the proposed controller is increased up to 65 times when in comparison to the open loop system.
Keywords: Control; Efficiency; Energy harvesting; Non-ideal excitation